Specifying a Gold Standard for the Validation of Fetal Fraction Estimation in Prenatal Screening. (1st September 2018) - Wald, Nicholas J; Lau, King Wai; Bestwick, Jonathan P; Old, Robert W; Huttly, Wayne J; Cheng, Ray
Abstract: BACKGROUND: An estimate of fetal fraction (FF) is needed for DNA-based screening for trisomy 21 and other aneuploidies, but there is no gold standard to validate FF measurement methods. We specify a gold standard and use it to validate a method of measuring FF (SeqFF) in singleton pregnancies. METHODS: The gold standard was a formula derived from 2 elements: ( a ) an estimate of the percentage of DNA fragments in maternal plasma from chromosome 21 (%Ch21) in pregnancies without trisomy 21, 18, or 13 (PU ) and ( b ) calculation of %Ch21 with increasing FF in trisomy 21 pregnancies (P21 ). The SeqFF method was evaluated by plotting regression lines of %Ch21 and SeqFF estimates of FF in 31 singleton male and 31 female trisomy 21 pregnancies and comparing the regressions with the reference line derived from the gold standard formula. RESULTS: The gold standard formula was P21 = (1/2)PU FF + PU, with FF expressed as a proportion, or converting %Ch21 to multiples of the median (MoM), P21 (MoM) = (1/2)FF + 1. Based on 3865 pregnancies, the PU was 1.2935%. The regression lines for trisomy 21 pregnancies with male and female fetuses were almost identical to the gold standard reference line (regression slopes in MoMs 0.52 and 0.50, respectively, compared with 0.50 for the gold standard reference line). CONCLUSIONS: The proposed gold standard can be used to validate different methods of estimating FF in singleton pregnancies. SeqFF is an accurate method of estimating FF.